Scoping Review: The Relationship between Screen Time and Behavioral Problems in Preschool-Age Children - Sangadi, Kyana Salapani; Hapsari, Indri; Pudjiati, Sri Redatin Retno (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Screen use has become a significant part of daily life for today’s preschool aged children. Gadgets are used for playing, watching, learning, and communicating. Previous research has found that the screen time of preschool aged children in Indonesia is well above the recommended duration. This may lead to the emergence of problem behaviors. The purpose of this scoping review is to study the relationship between screen time and problem behavior in Indonesian preschool aged children. The literature search in this study is done through several electronic databases, including Garuda, Sinta, and Google Scholar. We found 9 papers that focused on screen time and problem behavior in preschool aged children, with 2 qualitative studies and 7 quantitative studies. The results showed that there is a relationship between screen time and problem behaviors, specifically ones related to emotion, social skills, and hyperactivity/attention. Therefore, screen time in preschool aged children needs to be monitored in order to reduce the risk of problem behaviors. Di era digital ini, anak usia prasekolah sudah mempergunakan media layar untuk berbagai kegiatan sehari-hari, seperti bermain, menonton, belajar, dan berkomunikasi. Riset sebelumnya menemukan bahwa screen time anak prasekolah di Indonesia berada diatas rata-rata durasi yang direkomendasikan. Hal tersebut mungkin mempengaruhi kemungkinannya muncul masalah perilaku. Tujuan dari scoping review ini adalah untuk mempelajari hubungan antara screen time dan masalah perilaku pada populasi anak usia prasekolah di Indonesia. Pada penelitian ini, pencarian literatur dilakukan melalui database Garuda, Sinta, dan Google Scholar. Berdasarkan pencarian, ditemukan 9 studi yang mendalami topik screen time dan masalah perilaku dalam anak usia prasekolah. Studi terdiri dari 2 penelitian kualitatif dan 7 penelitian kuantitatif. Hasil menunjukan bahwa terdapat hubungan antara screen time dan masalah perilaku, khususnya yang berkaitan dengan emosi, sosialisasi, dan hiperaktivitas/atensi. Oleh karena itu, sangat penting untuk memperhatikan screen time pada anak usia prasekolah untuk mengurangi resiko masalah perilaku.